2018
DOI: 10.1007/s10953-018-0820-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acids and Sodium Chloride on d-Sorbitol in Aqueous Solutions at Different Temperatures: Volumetric and Acoustic Approach

Abstract: Apparent molar volumes and apparent molar compressibilities for d-sorbitol in (0.05, 0.1, 0.2 and 0.3) mol·kg−1 aqueous solutions of l-alanine, l-cysteine and l-histidine and NaCl have been determined from measurements of solution density at T = (288.15, 298.15, 308.15 and 318.15) K and sound velocity at T = 298.15 K, as a function of the concentration of the sugar alcohol. The data were used to obtain the limiting apparent molar volumes, limiting apparent molar compressibilities and the corresponding transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The four ionic liquids 186a-d (Figure 13), constituted by a morpholinium cation and an amino acid anion, were easily prepared 71 in 90-95% yield by neutralization of N-butyl-N-methylmorpholinium hydroxide with N-acetyl-L-amino acids (alanine, valine, leucine, isoleucine) and characterized by NMR, IR, and HRMS analyses (the optical rotation values were missing). In 2023, the same research group reported 72 the investigation of the thermophysical properties of aqueous solutions containing these ionic liquids by measuring density and sound speed. It was found that the ion-solvent interactions were mainly determined by the hydrophobicity of the amino acid anion.…”
Section: Figure 12 Ionic Liquids Based On L-proline Anionmentioning
confidence: 99%
“…The four ionic liquids 186a-d (Figure 13), constituted by a morpholinium cation and an amino acid anion, were easily prepared 71 in 90-95% yield by neutralization of N-butyl-N-methylmorpholinium hydroxide with N-acetyl-L-amino acids (alanine, valine, leucine, isoleucine) and characterized by NMR, IR, and HRMS analyses (the optical rotation values were missing). In 2023, the same research group reported 72 the investigation of the thermophysical properties of aqueous solutions containing these ionic liquids by measuring density and sound speed. It was found that the ion-solvent interactions were mainly determined by the hydrophobicity of the amino acid anion.…”
Section: Figure 12 Ionic Liquids Based On L-proline Anionmentioning
confidence: 99%